Propuesta de Promoción del Potencial Turístico de la Parroquia San José de Ancón - Sarmiento Iglesias, Marisela Vanessa (2013)
The Mining Camp Ancon, now San Jose Parish of Ancon located in the province of Santa Elena extends over an area of 78 km ² always visited by its nature, air and peace. Ancon recreates the atmosphere of a typical English village, much of its urban area, its architecture dates from the third decade of the last century, its buildings were built with high quality wood which is the only witness to an era that marked since 1911 the true start of oil exploitation in Ecuador. The order, punctuality and good manners are still practiced, as inheritance from the British and perpetuated through generations. Through research of this project is to promote the parish through which a proposal to take the tourist development of Ancon and could be beneficial to the people and that would provide more jobs and grow the socioeconomic status of the population. Another objective of this project is to provide Ancon as one of the main tourist attractions of the country as it has a very important story which recounts one of the first foreign arrivals to our shores and the first oil holdings.